2018
DOI: 10.1002/jcp.27473
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐cold acclimation improves the immune function of trachea and resistance to cold stress in broilers

Abstract: Acclimation can alleviate the damage caused by adverse environmental factors. To investigate the effects of cold stimulation on immunity in tracheal of broilers, 360 one-day-old chicks were raised at normal temperatures during 1-7 days. From 8 day, G1 (control) continued to be raised at normal temperatures, whereas G2 and G3 (treatment groups) were cold-stimulated at 3°C and 12°C below the temperature of G1, respectively. At 42 day, all the groups were subjected to a 24-hr acute cold stress, designated as S1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 49 publications
1
41
0
1
Order By: Relevance
“…Seasonality of the PED epidemic may link to environmental factors such as the drop of ambient temperature. Physiological stress experienced under cold exposure leads to a weakening of immune response [36] and increased Hsp70 levels [13,14]. It has been reported that Hsp70 could promote influenza A virus replication through modulates polymerase activity [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonality of the PED epidemic may link to environmental factors such as the drop of ambient temperature. Physiological stress experienced under cold exposure leads to a weakening of immune response [36] and increased Hsp70 levels [13,14]. It has been reported that Hsp70 could promote influenza A virus replication through modulates polymerase activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins (Hsps), molecular chaperones originally discovered based on their up-regulation in response to heat stress. Evidence is growing that exposure of cells and tissues to low ambient temperature leads to transcription and translation of heat shock proteins 70 KDa (Hsp70) [9][10][11][12][13][14]. Moreover, Hsp70 has been shown to be one key factor for multiple virus infection including rabies virus [15], porcine circovirus type 2 [16], porcine reproductive and respiratory syndrome virus [17], influenza A virus [18], dengue virus [19], infectious bronchitis virus [20], Epstein-Barr virus [21], ectromelia virus [22], hepatitis B virus [23], enterovirus A71 [24] and zika virus [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Broilers are also susceptible to spikes in cooler weather. Su et al noted that immunity in tracheal mucosa decreased in broilers exposed to acute 24-h cold stress from 20 °C to 7 °C [ 56 ]. Temperature stress from cold or heat, can cause oxidative stress and increase the expression levels of heat shock proteins, which can initiate an inflammatory response and decrease immune function [ 57 ].…”
Section: Challenges In Nae Productionmentioning
confidence: 99%
“…Tracheal defense function mainly depends on the integrity of its mucosa and the secretion of protective proteins [31]. To the best of our knowledge, most of the previous experiment reported that increasing stocking density linearly decreased intestinal barrier function [32], but there is rarely any report on the effects of high-stocking density on trachea barrier function.…”
Section: Discussionmentioning
confidence: 98%